A self-accelerated biocatalyst for glucose-initiated tumor starvation and chemodynamic therapy. Issue 93 (6th November 2020) - Deng, Fuan; Fan, Guiling; Yuan, Ping; Liu, Yibin; Huang, Chuyu; Zhao, Linping; Wang, Xin; Yu, Xiyong; Cheng, Hong; Li, Shiying
Abstract : A self-accelerated biocatalyst (Bio-Cat) was developed based on BSA and GOx crosslinked nanoproteins for glucose-initiated tumor starvation and chemodynamic therapy. Abstract : A self-accelerated biocatalyst (Bio-Cat) was developed based on BSA and GOx crosslinked nanoproteins for glucose-initiated tumor starvation and chemodynamic therapy. Bio-Cat could catalyze the glucose to elevate the intracellular H2 O2 level and accelerate the conversion of Fe 3+ /Fe 2+, resulting in an effective starvation therapy and an accelerated Fenton reaction for chemodynamic therapy.